Analisis Rembesan pada Bendung Tipe Urugan melalui Uji Hidrolik di Laboratorium FT Unsri - Sukir Man (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
Dam is used to raise water level and store water. One problem that often occurs is the presence of seepage at the dam. This study aims to determine the effect of soil particle size, high water level of the seepage velocity and seepage flow pattern on the dam. The method used in this study is the Darcy's law. The equipment used was Drainage and Seepage Tank. The results of this study indicate that the seepage velocity on sand 1 (medium sand) with water level 40 cm, 30 cm, and 25 cm is 8.4 x 10-4 cm / sec, 7.4 x 10-4 cm / sec and 6 x 10-4 cm / sec. At 2 sand (fine sand) with water level 40 cm, 30 cm and 25 cm is 3.58 x 10-4 cm / sec, 3.07 x 10-4 cm / sec, and 2.69 x 10-4 cm / sec. The results showed that the higher water level the faster seepage and the greater zize of a grain of soil more velocity.